Implementasi Desain Business Model Canvas Dalam Rangka Meningkatkan Kapasitas Bisnis Pada Usaha Mikro Kecil dan Menengah (UMKM) Pempek Umize - Syahzanan Sahilah; Ratna Meisa Dai; Rivani Rivani (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2025)
UMKM play a crucial role in the Indonesian economy. The purpose of this study is to examine the effectiveness of BMC in improving the capacity and development of Pempek Umizee's business in a systematic and comprehensive manner. The method used is descriptive qualitative. Data collection was carried out using observation, interviews, and documentation studies. Data analysis techniques employed the triangulation model. The research findings revealed a significant impact on overall business growth, evidenced by relatively high revenue. BMC helped Pempek Umizee become more adaptive, efficient, and responsive to market demands, strengthening branding, marketing, innovation, and operational management.